Is Auditor Financial Decision-Making Affected By Prior Audit Report Information? A Behavioral Approach - Hendri Mauliansyah; Fandi Bachtiar; Budi Safatul Anam (BE-HISZ : Journal of Economics and Accounting, 2025)
This study experimentally examines whether and how prior audit report information influences auditors’ financial decision-making. Motivated by behavioral auditing theory, we investigate whether exposure to favorable versus unfavorable prior audit reports affects auditors’ judgments of audit risk, materiality, and planned audit effort. Using a controlled experimental design, professional auditors are randomly assigned to conditions that manipulate the nature of prior audit report information while holding current-year financial evidence constant. Consistent with predictions from anchoring and confirmation bias theory, the results show that auditors exposed to favorable prior audit reports assess lower audit risk and plan less extensive audit procedures compared to auditors exposed to unfavorable prior reports. Additional analyses indicate that time pressure amplifies reliance on prior audit information, increasing the magnitude of anchoring effects. These findings provide causal evidence that prior audit reports serve not only as informational inputs but also as cognitive anchors that shape auditors’ professional judgments. The study extends behavioral auditing research by demonstrating how historical audit information systematically biases financial decision-making even when auditors have access to identical current-period evidence. From a practical perspective, the results suggest that audit firms and standard setters should implement structured debiasing mechanisms, such as independent risk reassessment and judgment review protocols, to mitigate the unintended behavioral consequences of relying on prior audit reports. Overall, this study contributes to the literature by clarifying the behavioral mechanisms through which prior audit information affects audit quality in complex audit environments.